THE SCOPE OF TRADITIONAL ACTIVITIES OF COMMERCIAL BANKS - N. I. Valentseva (Финансы: теория и практика)
The article highlights the scope of traditional commercial banks’ activities segment and stresses that monitoring and management in these areas allow to minimize risks. The author suggests criteria to evaluate the scope of this kind of activities as well as analyzes the relationship between loans and deposits in terms of their maturity in the Russian banking sector in 2016. The paper points out advantages of the suggested evaluation model based on the ratio of assets and liabilities of the bank if used to manage risks linked to the credit organization’s balance structure.